Perbedaan Tekanan Darah Antara Shift Pagi, Siang dan Malam Pada Perawat Di Ruang Intensive Cardio Vascular Care Unit (ICVCU) RSUD DR. MOEWARDI SURAKARTA - Insani, Fatma Nurul, Tarwaka, PGDip Sc, M.Erg, Anisa Catur Wijayanti, SKM., M.Epid (2015)
The hospital is an organisation which organizes health care facilities are working for 24 hours. With the 24 hour service is regulated activities with shift work system. The negative impact of shift work system on nurses can be exposed to several health problems one of which causes high blood pressure. The purpose of this study is to know blood pressure difference of between morning, afternoon and night shift to nurse in the room Intensive Cardio Vascular Care Unit (ICVCU) Dr. Moewardi's Hospital of Surakarta. This research is observational analytic research with cross sectional approach . The study population was a nurse in the room ICVCU totaling 24 nurses (8 nonshift nurses and 16 nursing shift). The data was analized with Kruskal-Wallis method. The results showed not significant with p value=0,198 that mean not difference in blood pressure between morning, afternoon and night shift to nurse in the room Intensive Cardio Vascular Care Unit (ICVCU ) Dr. Moewardi's Hospital of Surakarta.